2021
DOI: 10.3390/app11041847
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation against DDoS Attacks on an IoT-Based Production Line Using Machine Learning

Abstract: Industry 4.0 collects, exchanges, and analyzes data during the production process to increase production efficiency. Internet of Things (IoT) devices are among the basic technologies used for this purpose. However, the integration of IoT technology into the industrial environment faces new security challenges that need to be addressed. This is also true for a production line. The production line is a basic element of industrial production and integrating IoT equipment allows one to streamline the production pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Firewalls, intrusion detection systems, machine learning, etc. can be used to mitigate DRDoS attacks [ 179 ].…”
Section: Devices’ Vulnerabilities and Requirementsmentioning
confidence: 99%
“…Firewalls, intrusion detection systems, machine learning, etc. can be used to mitigate DRDoS attacks [ 179 ].…”
Section: Devices’ Vulnerabilities and Requirementsmentioning
confidence: 99%
“…Despite the fact that IoT offers several benefits in healthcare settings, one of the major challenges limiting its application are security threats, such as data theft, device hijacking, system attacks (e.g., Distributed Denial of Service or DDoS), data ownership disputes, etc. The interconnection between IoT-based devices with the internet makes them prone to cyber-attacks or hacks [ 82 , 83 ]. Moreover, the use of IoT-based devices requires the use of data storage, such as the cloud, as well as the transfer of a patient’s data through the internet, which raises issues regarding privacy and security [ 84 ].…”
Section: Computer-aided Diagnosis (Cad) and Internet Of Medical Thing...mentioning
confidence: 99%
“…A logistic regression (LR) algorithm can estimate the probability of a particular instance belonging to a specific class, and, for that reason, is frequently employed in classification problems regarding intrusion detection and spam filtering [21]. Furthermore, the study in [22] designed and implemented a security solution based on a LR algorithm and showed that it is possible to secure an IoT-based production line against DDoS attacks by using ML algorithms and commonly available tools for network traffic analysis and evaluation.…”
Section: Logistic Regression (Lr)mentioning
confidence: 99%
“…[ 15,21,22] Support Vector Machine Better performance in datasets with few classes and many instances per class. Scalable.…”
Section: Difficult To Perform Classification In Case Of Non-linearly Separablementioning
confidence: 99%